ESOP, Kepemilikan Institusional, Komite Audit, Komisaris Independen dan Dampaknya Pada Nilai Perusahaan Non-keuangan Indonesia - Chrissyani, Yohana Bunga; Sukoco, Y. djoko; Ariyani, Vivi (Jurnal E-Bis, 2025)
This study aims to prove again the significance of the influence of the internal mechanisms of Good Corporate Governance: the employee stock option plan (ESOP), institutional ownership (KI), audit committee (KA), and independent board of commissioners (PDKI) on firm value as measured by price to book value (PBV). The object of research is non-financial companies listed on the IDX for the period 2020–2022, with as many as 556 company samples using the purposive sampling technique. The results showed that the Employee Stock Option Plan (ESOP) and institutional ownership variables had a significant positive effect on firm value, the audit committee had no effect on firm value, and the independent board of commissioners had a significant negative effect on firm value.